Factors influencing the choice of antidepressants: A study of antidepressant prescribing practice at University psychiatric clinic in Belgrade - Marić Nađa P.; Stojiljković Dragan J.; Pavlović Zorana; Jašović-Gašić Miroslava (Vojnosanitetski Pregled)
Background/Aim. Antidepressants are a widely used class of drugs. The aim of this study was to investigate different aspects of antidepressant prescribing practice at University Psychiatric Clinic in Belgrade. Methods. This cross-sectional study was carried out by retrospective analysis of the patient's medical charts. The study included all patients with antidepressant prescribed at discharge during 2009 (n = 296). The evaluation was focused on patient- related factors (socio-demographic and illness related), psychiatrist-related factors (sex and duration of working experience) and drug related factors (type of antidepressant, dose, polypharmacy and reimbursement by national health insurance). Results. Antidepressants were prescribed for unipolar depression (F32-34, ICD X) either without comorbidity (46.2%) or with comorbidity (24.7%), mostly as a monotherapy (91% had one antidepressant), to the patients who were 65% female, aged 50.1 ± 8.9, most of them with 12 years of education (52.6%), married (69.3%) and employed (55.9%). The majority of patients had a history of two hospitalizations (Med 2; 25th-75th perc. 1-4) during nine years (Med 9; 25th-75th perc. 2-15) after the first episode of depression. Among them, 19% were found to be suicidal in a lifetime. The single most prescribed antidepressant was sertraline (20.4%), followed by fluoxetine (13.3%) and maprotiline (11.7%). Utilization of antidepressants was positively correlated with the rate of reimbursement (p < 0.01). The most prescribed antidepressant group was selective serotonin reuptake inhibitors (SSRI) (47.8%), followed by tricyclic antidepresants (TCA) (25.3%) and new antidepressants - venlafaxine, tianeptine, mirtazapine, bupropion, trazodone (15.1%). Most of the drugs were prescribed in doses which are at the lower end of the recommended dose-range. Regarding severity of the actual depressive episode, TCA were prescribed for severe depression with psychotic features, while SSRI were choice for episodes with moderate symptom severity (p = 0.01). Psychiatrists with longer working age (20-30 years) hesitated to prescribe new antidepressants in comparison to younger colleagues (p = 0.01). Conclusion. Economic issues in Serbia as developing country influence the choice of antidepressants, as well as a psychiatrist’s working age and severity of depression. However, SSRI are the drugs of the first choice, as it was shown in most of the developed countries nowadays.